27 Regional variations in myocardial T1 relaxation times in healthy adults at 1.5 and 3.0 TESLA. (26th April 2015) - Rauhalammi, S; Carrick, D; Mangion, K; Clerfond, G; Barrientos, P Hall; McComb, C; Radjenovic, A; Berry, C
Abstract : Background: Limited information is available on regional differences in myocardial T1 relaxation times in healthy adults. We used cardiac magnetic resonance (CMR) imaging at two field strengths, 1.5- and 3.0 Tesla (T), to assess regional distribution of T1, in milliseconds (ms), in myocardial regions-of-interest (ROIs) in healthy adults. Methods: Healthy adults without history of cardiovascular disease underwent CMR at 1.5 T (Avanto) and 3.0 T (Verio). T1 maps were acquired in three left ventricular (LV) short-axis slices, using an optimised modified Look-Locker inversion recovery (MOLLI) investigational prototype sequence (Siemens WIP 448). ROIs were delineated using the American Heart Association 16-segment model. Results: 80 consecutive volunteers (41 (51.3%) male, mean age 44 ± 18 years) underwent scans 1.5 ± 1.4 days apart. Because of artefacts related to cardio-respiratory motion and susceptibility effects, 44 (3.4%) segments imaged at 1.5 T and 71 (5.5%) at 3.0 T were excluded, respectively, with a preponderance occurring at the distal LV. Mean T1 values at 1.5 T/3.0 T were 946.5 ± 50.3 ms/1152.0 ± 54.9 ms. At 1.5 T there were regional differences across 16 segments (Table 1); T1 values from myocardial septal ROIs (956.7 ± 44.8 ms) were higher than non-septal ROIs (941.8 ± 52.0 ms, p < 0.001). T1 was lower in lateral ROIs (939.7 ± 54.1 ms) vs. non-lateral ROI (949.6 ± 48.1 ms, p < 0.005). The regional differences were similar at 3.0 T (Table 1). Conclusion: T1 values vary according to myocardial location. The explanation may be related to myocardial structure/function relationships and merits further study.